Dinamika fatwa produk keuangan syariah - Jaih Mubarok (State Institute of Islamic Studies (IAIN) Salatiga, 2013)
Fatwa (opinion of jurist/mufti) is developed by mufti/ulama as an instrument of Islamic law as well as guidance for ummah. Fatwa is considered as an actual instrument of Islamic jurisprudence because of certain reasons: a) qaul ulama (jurist’s opinion) as another source of Islamic law beside Quran and hadits; b) there is one single authority of fatwa institution in Indonesia; and c) it is a Mufti’s response towards real social problems in the society. In fact, some fatwas of National Sharia Board are in harmonize with National Acts (i.e. Act of Central Bank).